The Role Of The Teacher In Curriculum Development Islamic Education At Smps Islamic Assirojiyah Omben Sampang - Marsuki Fadli; Lusi Dian Nur Faiq; Buna'i Buna'i (Aqlamuna: Journal of Educational Studies, 2023)
Abstract: educators have duties and responsibilities for the learning process by conveying knowledge and various beliefs to students so that they implement their knowledge in everyday life. The success of the learning process can be seen from the applied curriculum, the curriculum has two sides, namely as a document and as an implementation. From the problems above, the researcher interpreted and created a title " the role of the teacher in curriculum development islamic education at smps islamic assirojiyah omben sampang." in this study, the researcher used qualitative and data obtained by observation, interviews and documentation. the formulation of the problem in research 1) what is the role of the teacher in the development of Islamic education at smps islamic Assirojiyah Omben Sampang. 2) what are the forms of teacher activity in the development of the Islamic Education curriculum at smps islamic Assirojiyah Omben Sampang. 3) what must be mastered by a teacher in developing the Islamic Education curriculum at smps islamic Assirojiyah Omben Sampang. The research aims at what are the roles of the teacher, the forms of activities and what must be mastered by the teacher in the development of the Islamic education curriculum. Abstract: educators have duties and responsibilities for the learning process by conveying knowledge and various beliefs to students so that they implement their knowledge in everyday life. The success of the learning process can be seen from the applied curriculum, the curriculum has two sides, namely as a document and as an implementation. From the problems above, the researcher interpreted and created a title " the role of the teacher in curriculum development islamic education at smps islamic assirojiyah omben sampang." in this study, the researcher used qualitative and data obtained by observation, interviews and documentation. the formulation of the problem in research 1) what is the role of the teacher in the development of Islamic education at smps islamic Assirojiyah Omben Sampang. 2) what are the forms of teacher activity in the development of the Islamic Education curriculum at smps islamic Assirojiyah Omben Sampang. 3) what must be mastered by a teacher in developing the Islamic Education curriculum at smps islamic Assirojiyah Omben Sampang. The research aims at what are the roles of the teacher, the forms of activities and what must be mastered by the teacher in the development of the Islamic education curriculum.